URBAN-RURAL DISPARITIES IN THE DETERMINANTS OF YOUNG NEETS: EVIDENCE FROM INDONESIA - Dimas Putra Hendika (Jurnal Ilmu Ekonomi dan Pembangunan, 2026)
Indonesia has the highest NEET rate in Southeast Asia, with 22.3% of its youth population categorized as NEET. This issue is crucial as Indonesia undergoes a demographic bonus, and ineffective utilization of this opportunity may lead to economic losses. Existing studies on NEET determinants in Indonesia have largely relied on pooled regression models and have not formally tested whether determinants differ between urban and rural labor markets. This study uses the August 2023 National Labor Force Survey (Sakernas) to estimate separate survey-weighted logistic regression models for urban and rural youth, and applies a Chow-type test to examine whether the coefficients are equal across the two settings. The results show that the determinants of NEET status differ significantly between urban and rural labor markets (p < 0.001). Health is the strongest predictor in both settings and does not differ significantly across locations. Marital status and tertiary education have stronger associations in urban areas, while gender and age group show stronger associations with NEET status in rural areas. These findings point to the need for policies that are tailored to the different structural conditions of urban and rural labor markets in Indonesia.